A new synthetic strategy towards 2, 4, 5-trisubstituted 1H-imidazoles and highly substituted pyrrolo[1, 2-c]imidazoles by use of α-azidochalcones via Michael addition-cyclization followed by Wittig reaction. Issue 48 (30th November 2017) - Adib, Mehdi; Peytam, Fariba; Rahmanian-Jazi, Mahmoud; Bijanzadeh, Hamid Reza; Amanlou, Massoud
Abstract: Efficient and facile protocols for the preparation of highly functionalized 1 H -imidazoles and 5 H -pyrrolo[1, 2- c ]imidazoles are described. Heating a mixture of an α-azidochalcones and N, N, N′, N′ -tetramethyl guanidine under neat conditions gave the corresponding 2, 4, 5-trisubstituted 1 H -imidazole via Michael addition-cyclization in excellent yields. Subsequently, the prepared 1 H -imidazoles undergo addition-Wittig reaction with acetylenic esters in presence of triphenylphosphine in dichloromethane to afford 5 H -pyrrolo[1, 2- c ]imidazoles in high yields. Graphical abstract: